PRINCIPLES OF EFFECTIVE NUTRITION IN SPORTS - Pardayev Yunus Sobirovich (Bright Mind Publishing, 2025)
Effective nutrition plays a crucial role in optimizing athletic performance, influencing energy levels, recovery, and injury prevention. Despite the growing body of research, significant gaps remain in understanding the specific nutritional needs across diverse sports disciplines. This study aims to explore the principles of effective nutrition in sports, focusing on athlete perspectives and practices. A qualitative, survey-based methodology was employed, with data collected from 30 athletes across various sports. Findings revealed that while athletes generally prioritize macronutrient intake, many lack knowledge regarding micronutrients and hydration strategies critical for performance enhancement. Nutrient timing and supplementation were found to be inconsistently utilized, highlighting a need for more tailored dietary interventions. The study underscores the importance of individualized nutrition plans, emphasizing both practical and psychological aspects of dietary adherence. The implications suggest that sports organizations and coaches should integrate nutrition education into training routines and provide athletes with personalized dietary strategies to optimize their performance. Further research should focus on refining these interventions, exploring the role of genetics and microbiome in nutrition, and assessing the effectiveness of personalized sports nutrition strategies. The findings contribute to bridging the knowledge gap in sports nutrition and offer practical guidance for future sports nutrition education and research.
Keywords: Sports Nutrition, Athletic Performance, Macronutrients, Micronutrients, Hydration, Nutrient Timing, Supplements, Personalized Nutrition, Athlete Education.